Rhetorical strategies in secondary news presentation by radio stations in Oyo State, Nigeria (2012)
Secondary gatekeeping—a practice where a news medium selects and broadcasts fragments of the contents of another, primary media—is a novel, but prevalent phenomenon especially in the Nigerian broadcast media. The practice, unlike primary gatekeeping, is yet to receive copious scholarly attention. This study, through a combination of In-depth Interviews and Documentary (Content) Analysis, explored the rationale for newspaper reviews as performed by Radio O-Y-O, Premier FM, and Splash FM, Ibadan, Oyo State, and the delivery strategies employed by presenters of the radio stations. The study is anchored on Monroe’s Motivated Sequence (MMS) as its theoretical framework. Findings show that the radio stations’ rationale for reviewing news contents of newspapers was to achieve increased audience base, gain improved market value, and earn financial profits. Major devices of delivery, aimed at sustaining audience interest, include dramatisation, paraphrasing and suspense, translations, and voice modulation and mimicking.